Upgrading Students' Engagement in English Online Learning Using the Zoom Platform - Martha, Yayu Nopriani (Universitas Islam Negeri (UIN) Mataram, 2024)
Abstract—The shift to online learning, propelled by the COVID-19 pandemic, has transformed how students engage in education, including English language learning. This paper investigates the factors that influence student engagement in English online learning through the Zoom platform. The study aims to analyze students' cognitive, emotional, and behavioral engagement while using Zoom, exploring both the challenges and opportunities that arise in an online environment. Data for the study were collected through surveys and interviews with English language learners, as well as through observations of online Zoom sessions. The results highlight key factors affecting engagement, such as the role of interactive tools, instructor presence, peer interaction, and technical issues. Recommendations for improving online engagement are also discussed.